Atypical femoral neck fracture after prolonged bisphosphonate therapy - Kwang-kyoun Kim; Young-wook Park; Tae-hyeong Kim; Kyung-deok Seo (Korean Society of Pathologists & the Korean Society for Cytopathology, 2020)
Of the drugs developed to prevent and treat osteoporosis, bisphosphonate has played a very important role in preventing osteoporotic fractures. However, case reports describing atypical femoral fractures in patients using long-term bisphosphonates have emerged. The majority of atypical femur fractures occurs in the lateral aspect of the subtrochanteric or femur diaphysis, which is explained by accumulation of tensile stress in these areas. Although the superior cortex of the femur neck withstands maximum tensile stress, to our knowledge, there have been only two reports (three cases) of atypical femoral neck fracture. In addition, none of those case reports revealed detailed pathology related to suppressed bone turnover rate. We encountered an incomplete femoral neck fracture and diagnosed it as "atypical" on the basis of the patient's lack of trauma and medication history and pathological findings. For patients with groin pain, minimal or no trauma, and a history of long-term bisphosphonate use, an atypical femoral neck fracture should be considered.